Hybrid Micro-Modeling Approach for the Analysis of the Cyclic Behavior of RC Frames - Blasi, Gianni; De Luca, Flavia; Aiello, Maria Antonietta (Frontiers in Built Environment, 2018)
The present study is aimed at developing a hybrid approach to consider the effect of concrete cracking on the hysteretic response of RC frames. The mechanical behaviour of the concrete is defined according to the smeared cracking approach, while discrete cracking surfaces are included in the geometrical model. The interface behaviour of the discrete cracking surfaces is defined by the combination of contact and cohesive elements. The proposed approach is adopted in ABAQUS to simulate an experimental test on a double cantilever column for the calibration of the numerical model. Therefore, a test conducted on a RC portal and modelled numerically for the first time is simulated. Numerical and experimental results are compared in terms of hysteretic force-displacement behaviour and cumulative dissipated energy, in order to assess the reliability of the proposed model in simulating the energy dissipation capacity of RC members subjected to lateral cyclic loading. The hybrid modelling approach proposed allows an accurate description of the stress distribution and a fairly satisfactory matching of the hysteretic behaviour with a reasonable compromise in terms of computational effort.